Healthy fitness zone: identification of body fat percentage, body mass index and aerobic capacity for students - Listiandi, Arfin Deri; Budi, Didik Rilastiyo; Suhartoyo, Topo; Hidayat, Rohman; Bakhri, Rafdlal Saeful (Universitas Nusantara PGRI Kediri, 2020)
This study aimed to overview student fitness as detected from the Healthy Fitness Zone with the aspects measured were Body Fat Percentage, Body Mass Index, and Aerobic Capacity. This research method is descriptive correlational. The subjects of this study were 68 physical education students. The norm used in this study is the Fitnessgram to observe the Healthy Fitness Zone (HFZ) in students. The results showed that the students' fitness was high-grade with the percentage of BFP who were in the HFZ criteria of 91.2%, BMI in the HFZ criteria of 72.1%, and Aerobic Capacity in the HFZ criteria of 80.9%. Meanwhile, the correlation shows a significant relationship, with the value of Correlation (R) = 0.570 and sig. = 0.000 <0.05. It can be concluded that there is a significant relationship between Body Mass Index and Body Fat Percentage with the Aerobic Capacity of physical education students.